CEO Salary Increases May be Rational After All: Referents and Contracts in CEO Pay - Miller, Daniel J. (Academy of Management Journal, 1995)
Studies investigating the relationship between executive compensation and firm performance, firm size, or both have had consistently low explanatory power. The present study uses Forbes data for 1983?89 and shows that nonparametric models, comparing the ranks of firms within industries, more accurately reflect changes in CEO compensation. There was no support for a linear relationship between performance and such changes but strong support for an increasing, convex relationship.